2017
DOI: 10.1161/hypertensionaha.116.08964
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hydrogen Sulfide–Mediated Vasodilation Contributes to Microvascular Endothelial Dysfunction in Hypertensive Adults

Abstract: Reductions in hydrogen sulfide (H2S) production have been implicated in the pathogenesis of vascular dysfunction in animal models of hypertension; however, no studies have examined a functional role for H2S contributing to microvascular dysfunction in hypertensive (HTN) adults. We hypothesized that endogenous production of H2S would be reduced, impaired endothelium-dependent vasodilation would be mediated by reductions in H2S-dependent vasodilation, and vascular responsiveness to exogenous H2S (Na2S) would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 51 publications
4
60
0
Order By: Relevance
“…for the blood pressure measurements. Consistent with the ability of ACh to induce vascular relaxation by stimulating endothelial nitric oxide (NO) production, 12,17 ACh (0.1 nmol/L-10 μmol/L) dose-dependently induced the relaxation of aortic rings pre-constricted with 1 μmol/L phenylephrine in the control group whereas AngII significantly decreased the ACh-induced relaxation ( Figure 1D).…”
Section: Hnk Attenuates Angii-induced Hypertension and Vascular Endsupporting
confidence: 67%
See 1 more Smart Citation
“…for the blood pressure measurements. Consistent with the ability of ACh to induce vascular relaxation by stimulating endothelial nitric oxide (NO) production, 12,17 ACh (0.1 nmol/L-10 μmol/L) dose-dependently induced the relaxation of aortic rings pre-constricted with 1 μmol/L phenylephrine in the control group whereas AngII significantly decreased the ACh-induced relaxation ( Figure 1D).…”
Section: Hnk Attenuates Angii-induced Hypertension and Vascular Endsupporting
confidence: 67%
“…7,9,10 Alternatively, numerous studies have demonstrated that CSE-mediated H 2 S generation induces endothelium-dependent vasodilation and improves cardiovascular function and integrity. 11,12 Histone deacetylase 6 (HDAC6) is implicated in the pathophysiology of hypertension-related vascular diseases. 13,14 HDAC6 plays a significant role in the cardiac dysfunction mediated by angiotensin II (AngII), an inducer of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, treatment with NaHS increased H 2 S plasmatic levels in the Preg+NaHS group. Decreased levels of H 2 S are related to hypertension; however, we surprisingly found increased H 2 S plasmatic levels in HTN‐Preg. We suggest that desoxycorticosterone acetate (DOCA)‐induced hypertension may trigger mechanisms that increase H 2 S production, as a compensatory response, since it has been shown that H 2 S may exert protective effects during cardiovascular disorders .…”
Section: Discussionmentioning
confidence: 47%
“…"H 2 S-Rich" and "H 2 S-Poor" Pathophysiological Conditions H 2 S has been implicated in the pathogenesis of multiple diseases, as overviewed in review articles. These range from cardiovascular diseases (e.g., myocardial reperfusion injury, cardiac hypertrophy, heart failure, atherosclerosis, hypertension) (Predmore et al, 2012b;Polhemus and Lefer, 2014;Ahmad et al, 2015;Meng et al, 2015aMeng et al, , 2016Shen et al, 2015;Wang et al, 2015a;Cao and Bian, 2016;Kanagy et al, 2017;Greaney et al, 2017) to various neurologic diseases (e.g., stroke, neuroinflammation) (Wang et al, 2014a;Bhatia, 2015;Kida and Ichinose, 2015;Wallace et al, 2015;Sen, 2017) and metabolic diseases (e.g., diabetes mellitus) (Desai et al, 2011;Szabo, 2012;Okamoto et al, 2015;Carter and Morton, 2016) to various forms of local and systemic inflammation (e.g., hemorrhagic shock, septic H 2 S Donors and H 2 S Biosynthesis Inhibitors shock, burn injury) (Wagner et al, 2009;Coletta and Szabo, 2013;McCook et al, 2014;Akter, 2016).…”
Section: H 2 S As An Endogenous Biologic Mediatormentioning
confidence: 99%
“…Despite its low potency that requires millimolar concentrations in cell-based assays, aminooxyacetic acid (AOAA), also known as (carboxymethoxy)amine hemihydrochloride (CHH) or hydroxylamine-O-acetic acid hemihydrochloride (Table 2), was extensively used for years to inhibit CBS not only in vitro but also in vivo (e.g., Mudd et al, 2011;Szabo et al, 2013). Interestingly, a recent human study using local acetylcholine perfusion and measurement of blood flow by laser Doppler flowmetry found that AOAA reduces acetylcholine-induced vascular relaxations, implicating H 2 S as a contributor to the regulation of vascular tone (Greaney et al, 2017).…”
Section: Pharmacological Inhibitors Of Cystathionine-b-synthasementioning
confidence: 99%